(untitled) (The Review of Diabetic Studies, 2022)
Cholistan Desert is a sandy desert located in southern Punjab, Pakistan. The area is rich in more than 64 medicinal plants among 138 plant species. It is noteworthy that this remote desert lacks modern health care facilities and its inhabitants are dependent on locally-available plant species for the treatment of acute and chronic illnesses. Medicinal plants, traditionally have been ideal sources of remedies for the management of many non-communicable diseases; most modern prescriptions drugs have their origins from plants. Diabetes is increasing at an alarming rate in the past few decades. Whereas medicinal plants are used globally, the specific properties of only a few have been identifies scientifically. Similarly, little scientific evidence exists that confirms the efficacy of the medicinal plants of this region for diabetes management. Ethnobotanical studies show that locally-available medicinal plants do have anti-diabetic potential. We reviewed the medicinal properties of 36 of these plants. Several ingredients derived from these plants have chemical constituents that demonstrate anti-diabetic activity, thereby validating their importance for the management of diabetes.